The quality of sport- recreation services - Widawska-Stanisz, Agnieszka (Quality in Sport, 2015)
There is a description of sport- recreation services and their quality presented in this article. The most important factors determining the high quality of providing services and the meaning of quality standards in the process of providing sport- recreation services are shown. There are some research results conducted among residents of Silesia province on the offers of sport – recreation companies and the qualities of their services.